Kolb’s Experiential Learning Theory Application in Home-based Laboratory Activities of Science Major Students in Microbiology Subject - Allauigan, Merry Ann; Melad, Kim; Beltran, Odessa; Jamoral, Rockangel; Bete, Aisie (FKIP Universitas Lampung, 2023)
Kolb’s Experiential Learning Theory Application in Home-based Laboratory Activities of Science Major Students in Microbiology. Objectives: This paper describes the experiences of science major students in doing their home-based laboratory activities in microbiology during the onslaught of the COVID-19 pandemic. It is framed on Kolb’s experiential learning theory. Methods: Using criterion sampling, nine BSEd Science major participants were interviewed face-to-face to describe their experiences using phenomenological hermeneutics. Kolb’s theoretical constructs were used to thematically analyze the participants’ responses. Findings: It revealed that students prefer doing laboratory experiments at school than at home due to the availability of laboratory materials. Students experience difficulty in doing home-based laboratory activities due to the difficulty of providing alternative laboratory materials to complete the laboratory tasks at home. Nevertheless, students gain self-development skills such as communication skills and resourcefulness. Conclusion: Science major students in microbiology have developed skills in adapting to the changes brought by the COVID-19 pandemic, thereby, they developed flexibility and resourcefulness in accomplishing their home-based laboratory activities. Keywords: experiential learning theory, home-based laboratory activities, microbiology, phenomenology, science majors.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202333